2015
DOI: 10.1002/phar.1662
|View full text |Cite
|
Sign up to set email alerts
|

Possible Rivaroxaban Failure during the Postpartum Period

Abstract: Rivaroxaban, a factor Xa inhibitor, is a direct-acting oral anticoagulant (DOAC) indicated for the treatment of deep vein thrombosis (DVT) and pulmonary embolism (PE), and for reducing the risk of DVT and PE recurrence. To our knowledge, no data are presently available to guide DOAC dosing in the postpartum period when pharmacokinetic and pharmacodynamic changes induced by pregnancy have an impact on drug clearance and increase hypercoagulability for a period of 6-8 weeks after delivery. We describe the case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The recent addition of factor Xa inhibitors to anticoagulant agents is not without fault (i.e., failure, bleeding, and lack of reversal agents), as demonstrated in this case report and other papers [6, 7, 12]. The risk factors for failure of anticoagulation therapy are vast and vary from patient to patient; pharmacodynamics, pharmacokinetics, metabolism, and elimination all have a hand in how a drug interacts in a given patient and are further discussed below [1315].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The recent addition of factor Xa inhibitors to anticoagulant agents is not without fault (i.e., failure, bleeding, and lack of reversal agents), as demonstrated in this case report and other papers [6, 7, 12]. The risk factors for failure of anticoagulation therapy are vast and vary from patient to patient; pharmacodynamics, pharmacokinetics, metabolism, and elimination all have a hand in how a drug interacts in a given patient and are further discussed below [1315].…”
Section: Discussionmentioning
confidence: 52%
“…A thorough literature review revealed little in the way of reports of rivaroxaban failure in the treatment of DVT, although a few case reports in which potential rivaroxaban failure is noted have emerged recently [6, 7]. Postmarketing surveillance is clearly an important factor in the further development, safety, and efficacy of any novel drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we suggest that practitioners carefully weigh the risks and benefits when selecting these medications. We note that Rudd et al have reported independently on possible rivaroxaban failure in patients treated during the postpartum period, possibly due to pharmacokinetic alterations seen in the postpartum period that can contribute to decreased drug exposure and reduced anticoagulant efficacy [16]. In fact, rivaroxaban is well known to be metabolized by the cytochrome P450 isoenzyme CYP 3A4 and binds to P-glycoprotein; hence, leading to risks of pharmacokinetic interactions that may alter its anticoagulant properties [17].…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulation decreases the risk of recurrent venous thromboembolism (VTE) in patients with DVT to 6.3/100 patientyears. 1,2 However, this is after the discontinuation of anticoagulant therapy. 2 The risk of recurrent VTE is not static and decreases over time.…”
mentioning
confidence: 99%